Constructive Response Vs. Multiple-Choice Tests In Math: American Experience And Discussion (Review) - Stankous, Nina V. (European Scientific Journal, ESJ, 2016)
This study investigates and compares multiple-choice and constructive-response test formats for assessments in mathematics. This topic has been researched and debated for many years by students, educators, and politicians. Even between students there is a wide range of disagreement between which test format is preferred. Prior research has revealed both benefits and disadvantages for both formats. The study found that although multiple-choice tests are often used to measure student and teacher performance in math education, constructive-response test formats better represent student learning. Some factors that will be discussed are the â€œguessingâ€ problem, partial credit, grading efficiency, and the ability to cover topics.